Analysis of Heavy Metals in Traditional Herbal Medicine (Jamu Pegal Linu) Circulating in Banda Aceh City - Farida, Mutia; Safrina, Nurul; Kurniaty, Rina; Azhari, Saiful; Mahmudi, Mahmudi; Yusuf , Muhammad (Journal of Pharmaceutical and Sciences, 2025)
Background: Jamu pegal linu (traditional Indonesian herbal medicine for muscle and joint pain) is widely consumed to relieve muscle and bone discomfort. However, there are concerns about heavy metal contamination, particularly lead (Pb) and mercury (Hg), in some products circulating in Banda Aceh City. Such contamination poses serious health risks, including organ damage and poisoning, necessitating thorough analysis to ensure product safety. Objective: This study aimed to detect and measure Pb and Hg levels in jamu pegal linu samples sold on Diponegoro Street, Banda Aceh, and compare them with the safety limits set by the Indonesian Food and Drug Authority (BPOM RI). Methods: A total of 23 samples were qualitatively analyzed using KI, NaOH, and HCl reagents (for Pb) and HNO₃ and KI (for Hg). Positive samples were further analyzed quantitatively using Atomic Absorption Spectrophotometry (AAS). Method validation included linearity, precision, accuracy, LoD, and LoQ assessments. Results: Qualitative testing revealed Pb and Hg contamination in 12 samples. Pb levels ranged from 1.45–9.17 mg/kg (below BPOM’s threshold of ≤10 mg/kg), while Hg levels ranged from 0.14–1.37 mg/kg, with six samples exceeding the safe limit (≤0.5 mg/kg). The highest Hg concentration (1.37 mg/kg) was found in an unregistered product. Conclusion: Most jamu pegal linu products in Banda Aceh contain heavy metals, particularly Hg, at unsafe levels. Strict regulatory oversight, especially for unregistered products, is crucial to safeguard public health.